Identification of Bioactive Compounds in Cassia Alata Using GC-MS and Their Potential Against Microorganisms That Cause Skin Infections - Khairiah, Ardian; Agustin, Olivia; Dasumiati (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Cassia alata is widely used in traditional medicine for treating skin infections, yet its antifungal properties and chemical constituents remain underexplored. This study aimed to identify bioactive compounds in C. alata leaves and evaluate their antioxidant and antimicrobial potential. Phytochemical analysis was performed using Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Antimicrobial efficacy was tested against Staphylococcus aureus, S. epidermidis, Malassezia furfur, and Trichophyton rubrum at extract concentrations of 6; 9; 12; and 15%. GC-MS analysis revealed six major peaks, with myo-inositol identified as the dominant compound. The extract exhibited weak antioxidant activity, with an IC₅₀ value of 174.9 ppm. However, significant antifungal activity was observed, particularly against M. furfur and T. rubrum, with the most effective inhibitory concentrations at 12% and 15%, respectively. Despite its modest antioxidant effect, C. alata leaf extract demonstrates promising antifungal potential, especially against common fungal pathogens associated with skin infections. These findings support the traditional use of C. alata and highlight its potential as a natural antifungal agent.